Thymus vulgaris L. extract has antimicrobial and anti-inflammatory effects in the absence of cytotoxicity and genotoxicity - Oliveira, Jonatas Rafael de [UNESP]; de Jesus Viegas, Daiane [UNESP]; Martins, Ana Paula Réquia [UNESP]; Carvalho, Cláudio Antonio Talge [UNESP]; Soares, Cristina Pacheco; Camargo, Samira Esteves Afonso [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; de Oliveira, Luciane Dias [UNESP] (Elsevier, 2017)
Objectives This study evaluated the biological effects of the T. vulgaris L. extract., such as antimicrobial activity on planktonic cultures and mono- and polymicrobial biofilms, cytotoxicity, anti-inflammatory activity and genotoxicity. Methods Monomicrobial biofilms of Candida albicans, Staphylococcus aureus, Enterococcus faecalis, Streptococcus mutans and Pseudomonas aeruginosa and polymicrobial biofilms composed by C. albicans with each bacterium were formed for 48 h and exposed for 5 min to the plant extract. Murine macrophages (RAW 264.7), human gingival fibroblasts (FMM-1), human breast carcinoma cells (MCF-7) and cervical carcinoma cells (HeLa) were also exposed to the plant extract for 5 min and the cell viability were analyzed by MTT, neutral red (NR) and crystal violet (CV) assays. Interleukin-1 beta (IL-1β) and tumor necrosis factor alpha (TNF-α) produced by RAW 264.7 was quantified by ELISA, after 24 h exposure to the plant extract, both in the absence and presence of lipopolysaccharide (LPS) from Escherichia coli. Genotoxicity of the plant extract was evaluated by micronucleus formation (MN) in 1000 cells. The results were analyzed by T-Test or ANOVA and Tukey's Test (P ≤ 0.05). Results All biofilms showed significant reductions in CFU/mL (colony-forming units per milliliter). Cell viability was above 50% for all cell lines. Anti-inflammatory effect on the synthesis of IL-1β and TNF-α was observed. The MN was similar or lower than the control group in all cells. Conclusions T. vulgaris L. extract was effective against all biofilms, promoted high cell viability, anti-inflammatory effect and presented no genotoxicity.
Keywords: Anti-inflammatory activity; Antimicrobial activity; Biofilms; Cytotoxicity; Genotoxicity; Thymus vulgaris l